Improving Metro Manila Metro Rail Transit operations by optimizing train capacity and headway - Ebia, Eric O. III; Ramirez, Pauline Shei V.; Sigua, Ricardo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The paper presents an approach on minimizing the congestion inside the stations and trains of the Metro Manila Metro Rail Transit line (MRT3) by determining the optimum line capacity and headway that can serve the passenger volume demand during peak hours. Through a simultaneous survey, the researchers identified the peak hour passenger volume demand, capacity of an individual coach, actual headway and other specifications of the MRT3 line. Based on these sets of data, the researchers proposed the optimum line capacity and headway combination under two conditions: crush loading and a condition which considers the comfort and safety of the passengers. For crush loading, the optimum train capacity requires an upgrade to 4 coaches per train with a line headway of 4.1 minutes while for the condition considering the comfort and safety of the passengers, the same upgrade is needed with a line headway of 1.5 minutes.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Street-railroads -- Passenger traffic; Street-railroads -- Philippines -- Manila Metropolitan area; Passenger trains